IMPLEMENTASI PERATURAN DAERAH NOMOR 10 TAHUN 2012 TENTANG PENGELOLAAN TANGGUNG JAWAB SOSIAL PERUSAHAAN DI KOTA CILEGON - Rahmatullah Rahmatullah (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2017)
This study discusses the implementation of local regulations No. 10 year 2012 on managing Corporate Social Responsibility in Cilegon. This type of study is descriptive, using qualitative approach. Results of the study illustrates that change has not been implemented, since it was passed on April 30, 2012. There are 2 (two) clauses article in particulary regarding Perda operational costs and recruitment patterns of administrators through the fit and proper test. The study recommends revisions to some article that impedes the passage of Perda, in addition to the importance of involving stakeholders’ executor (company) in the formulation of article so as to accommodate the needs of the Government, enterprises and society.Key Words: Implementation, Local Regulations, Corporate Social Responsibility